High speed MDM-Ro-FSO communication system by incorporating AMI scheme. Issue 3 (3rd July 2019) - Chaudhary, Sushank; Amphawan, Angela
ABSTRACT: Radio over Free Space Optics (Ro-FSO) is a promising technology to provide broadband services in rural areas as next-generation communication networks. This work is focused on adopting alternate mark inversion (AMI) encoding for mode division multiplexing (MDM)-based Ro-FSO networks. Two independent channels, each carrying 2.5Gbps-10GHz data, are transmitted on Hermite Gaussian (HG) 00 and Laguerre Gaussian (LG) 00 modes over 14 km of free space optical (FSO) link.